Exploration and practice of ideological and political education in biochemistry and molecular biology for cultivation of ethical and medical talents - Zhang Chunjing; Liu Ying; Qi Xiaodan; Wang Xiaolong; Zhao Zhenglin (SHS Web of Conferences, 2023)
Combine the learning characteristics of medical specialty and the core socialist values. Ideological and political education is integrated into the teaching of biochemistry and molecular biology. We will strive to cultivate medical talents of the new era with excellent medical skills, noble medical ethics, the patriotism, concern for the people's livelihood and dedication for the society, guided by "professionalism", "practicing ability" and "social adaptation". The talent training of medical university bears the important task of training medical workers with noble medical ethics, exquisite medical skills and humanistic spirit [1]. Biochemistry and Molecular Biology is an important basic and compulsory course for medical majors. Its relevant theories and technologies have penetrated into all fields of basic medicine and clinical medicine. This course contains rich ideological and political education elements, which are closely combined with clinical practice and daily life, so that students can more vividly and concretely grasp the knowledge and feel the essence of the thought. The implementation of curriculum ideological and political education is helpful to improve the humanistic quality of medical students and professional ethics of doctors. This paper explores and practices the implementation methods of curriculum ideology in biochemistry and molecular biology. It also integrates the elements of moral education into daily teaching guided by "professional spirit", "practicing ability" and "social adaptation", aiming to continuously improve the effect of education and ultimately contribute to the cultivation of medical talents with both moral and medical skills.